Open Teaching: research and practice on open, innovative and engaging pedagogies - Nascimbeni, Fabio (Journal of E-Learning and Knowledge Society, 2021)
I-WhenUNESCOintroducedtheOERconceptandacoupleofyearslatertheOECDsuggestedtogiveknowledgeawayforfree(OECD,2007),we,asopeneducators,believedthatthiswastheavalanchewhichwehadbeenwaitingforandwhichwehadbeenexpectedtoarriveforalongtime.Today,attheendofapandemicyear2020,weknowthatwhatwehadbeenthinkingofasavalanche,hadjustmerelybeenatinysnowdrizzlecomparedtothehugeandrapid,andunprecedentedtectonicshiftsinthelandscapeofourhighereducationinstitutionswhichhadbeencausedthroughthenear100%substitutionsofwhathadbeenthegoodoldpresentialEuropeanuniversitythroughonlinemodes.Wepublishthisspecialissueonteachingandlearningintheopeninthisveryspecialtimeandareawarethatnothingsafeandsecurecanbesaidintermsofuptakeandhowthenextandnewnormalwilllooklikeinhighereducation.Thisistruefortheuseofdigitaltechnologyatlargeaswellasforthefurtherdeepeneduptakeofopeneducationpracticeinhighereducationinparticular.
Keywords: editorial; Emerging; Scopus(2)